Astronomy and the Climate Crisis - Cooke, Antony (Astronomers' Universe,, 2012)
Climate change is one of the most hotly debated issues of today. Increasing global temperatures will impact all of us. There are more questions than answers, however, and sweeping statements on the subject made by public figures, often with little scientific understanding, only further confuses public opinion. Astronomical factors, apart from passing references to the Sun, are given short shrift in relation to climate change. However, they might be amongst the major determinants of it.  A presentation of those that have been studied that some scientists suspect might be involved are featured in this book. Included is an in-depth look at the physics of climate itself, the potential effects of the Sun, solar storms, sunspots, solar variability, the magnetosphere, solar cycles, influences of nearby planets, orbital factors, cosmic rays, possible galactic influences, monitoring from space, even climate change elsewhere in the solar system, and much more. The greatest challenge climate change scientists face is determining actual world climate statistics and analyzing the historical record. Another challenge lies in evaluating all of the various theories that have been proposed. Is the current climate crisis completely human-induced, as some very credible sources say, or only partly human-induced.? Is carbon dioxide even the real threat? If not, what is? Astronomy and the Climate Crisis is a serious attempt to reconcile the various scientific climate change studies, highlighting in particular the astronomical factors that are possibly hidden culprits. This book can help you to become informed and join the debate. You might be very surprised at what you find out!  .